2019
DOI: 10.1002/slct.201902124
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Hepatotoxicity of Flavonoids and Their Metal Complexes Through Co‐Administration of β‐Cyclodextrin

Abstract: The in vivo determination of radical scavenging activity of flavonoids (Fls) and their metal complexes (M‐Fls) through co‐administration of 2‐hydroxypropyl beta‐cyclodextrin (HP‐βCD) was determined. The flavonoids morin (mo), quercetin (quer), primuletin (prim), their Cu (II) and Fe (III) complexes were selected to explore their radical scavenging potential. Metal complexes of flavonoids (M‐Fls) showed better radical scavenging activity RSA when injected to rats than corresponding flavonoids. The RSA is improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…In agreement with these results, the present findings showed that the flavonoid compounds present in LPE such as narirutin, hesperidin, and nobiletin, have the ability to reduce the oxidative stress induced by CPA in POF rats via enhancement of antioxidant status and reduction of lipid peroxidation levels. have been several previous studies of similar findings [10,50].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In agreement with these results, the present findings showed that the flavonoid compounds present in LPE such as narirutin, hesperidin, and nobiletin, have the ability to reduce the oxidative stress induced by CPA in POF rats via enhancement of antioxidant status and reduction of lipid peroxidation levels. have been several previous studies of similar findings [10,50].…”
Section: Discussionsupporting
confidence: 71%
“…The fruit contains a high concentration of phenolic chemicals, including flavonoids such as hesperidin, naringin, and naringenin and flavones such as diosmin [9]. These compounds exhibit many pharmacological actions in the body and are scientifically confirmed to confer positive health effects to limit the developing of various illness due to the abundance of vitamins, minerals, and other active ingredients related to antioxidant, anti-inflammatory, antiatherosclerotic, antiseptic, antifungal, anticarcinogenic, antimutagenic and hepatoprotective actions, and they boost the body's immune and cardiovascular system [10,11]. Citrus fruits can protect the human body from injury caused by ROS by reducing the loading of free radicals and/or enhancing the endogenous antioxidant protection system [12].…”
Section: Introductionmentioning
confidence: 99%
“…The blood lipid profile has been used as an indicator for liver injury (Buness et al., 2014). The decrease in total lipids along with high values of HDL‐c due to a high dose of MD indicates an increase in the regeneration process leads to repair of hepatic and renal tissue damage induced by paracetamol (Jabeen et al., 2019). Phenolic compounds and other minerals in Medicago sativa had been reported to normalize the blood cholesterol level by reducing intestinal absorption of cholesterol and also decreases atherosclerosis (Cohen et al., 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a huge number of reports have been presented about the medical activities of naringin and rutin (El‐desoky et al., 2018; Gullón et al., 2017). As a result, the flavonoids have fascinated much attention of the scientists because they showed hepatoprotective activities and the therapeutic properties such as antioxidant, anti‐inflammatory, anticarcinogenic, and antiaging (Chen et al., 2020; Jabeen et al., 2019; Maleki et al., 2019; Vukovic et al., 2018). However, the peel of citrus fruits contains the abundant proportion of flavonoid as compared to other parts of the fruit.…”
Section: Introductionmentioning
confidence: 99%